AR-OOP: Augmented Reality-based Mobile Learning Application for Learning Object-Oriented Programming - Hang, Lai Yip; Romli, Rohaida; Mohd Muhaiyuddin, Nadia Diyana (Multidisciplinary Applied Research and Innovation, 2023)
Nowadays, Object-Oriented Programming (OOP) is vital for modern software development. Practically, learning and understanding concepts of Object-Oriented Programming (OOP) is always difficult to students, especially the novices, and even for educators who teach the concepts, because these concepts are usually abstract and hard to image. Over the years, there have been various methods to support learning of these concepts including through mobile applications. Practically, mobile learning applications benefit users as they able to engage the course content and allow students to progress at their own pace. Additionally, with the emerging of Augmented Reality (AR), it allows the concepts of OOP can be visualized in a graphical way which enables novice learners to understand the fundamentals and relationship of objects clearly and thus understand the concepts at a first glance. Thus, this project proposes a mobile learning application that utilizing AR, namely AR-OOP to support novice in learning basic concepts of OOP. The AR-OOP consists of features such as View Notes, Do Quick Practice and Quiz, Learn OOP topics via AR Tutorial as well as view history of attempted quizzes. As of to access the functions of Do Quiz, AR Tutorial and View History, a user needs to register and login successfully. The AR Tutorial comprises three topics which are inheritance, polymorphism and encapsulation. The learning contents of these topics are presented in AR that provides an immersive digital experience in which digital objects are placed on top of real-world objects of environments. For example, in the inheritance topic, the hierarchical class diagrams are linked with their respective instances or objects to show how their relationships and interaction can be seen clearly supported with a feature to superimpose digital media atop physical objects. As to prove a validity of the AR-OOP, an evaluation was conducted to measure its usability, satisfaction, user interface and performance. The results have shown that most of the respondents provide very positive responses in all the measurements parameters. Generally, the AR-OOP is able to provide an immersive hybrid learning environment that allows the novice learners to tune into the concepts of OOP via interactive visualization.